Indirect targeting of MYC and direct targeting in combination with chemotherapies are more effective than direct mono-targeting in triple negative breast cancer - Negesse Mekonnen; Hobin Yang; Nirmal Rajasekaran; Kyoung Song; Yoon-La Choi; Young Kee Shin (Translational Oncology)
MYC amplification is disproportionally elevated in triple-negative breast cancer (TNBC) compared to other subtypes of breast cancer. Indeed, MYC has long been considered an undruggable oncogene using conventional drug design strategies or small molecules. We hypothesized that targeting MYC using asymmetric siRNA (asiRNA) alone or in combination with chemotherapeutic agents or indirectly via BRD4 and RRM2, may curb its oncogenic behavior. We developed paclitaxel-, doxorubicin-, and cisplatin-resistant MDA-MB-231 cells to study MYC's role in upregulating DNA repair genes during drug resistance development. Our results showed that the knockdown of either MYC or RRM2 downregulated both RAD51 and PARP1 but increased γH2AX. The cytotoxic effect of RRM2 knockdown was significantly (p < 0.05) higher than that of direct MYC knockdown. The knockdown of BRD4 was more effective than the direct knockdown of MYC in downregulating MYC protein. The combined use of asiRNA-VP (Vinylphosphonate) with dacomitinib or talazoparib was synthetic lethal in TNBC cell lines. Compared to chemotherapy-sensitive cells, resistant cells showed overexpression of MYC, RRM2, RAD51, and PARP1 proteins upon chemotherapy treatment, but downregulated in cells treated with asiRNA-VP combination. We confirmed that MYC knockdown upregulated cFLIP, BCL2, STAT1, pSTAT1, STAT2, and cleaved saspase-3 in both TNBC and non-small cell lung cancer (NSCLC) cell lines. Finally, we recommend a combination treatment approach that synergizes with MYC inhibition rather than monotherapy or indirect targeting via upstream regulators such as the BRD4 and RRM2 genes or selective modulation at the protein level to suppress anti-apoptotic genes (cFLIP and BCL2) at the same time.